Cult of Shiradi sai baba in cultural domain of Jaffna: cultural inquiry on religion and worship - Srikanthan, S.; Selvakumar, T. (South Eastern University of Sri Lanka, 2023)
Religion and its associated worship traditions are one of the creations of human culture. Renowned anthropologist, E.B. Tylor defined religion as belief in spiritual beings. Numerous religious traditions have been originated in different periods of the world history and have being spread among the people. The South Asia is an origin center of foremost religions such as Hinduism, Buddhism, Jainism and Sikhism in the world. It could be observed in the religious history of South Asia that new religious cult are being formed through religious syncretism process during the various historical period of the region. In this context, this present study attempts to make a cultural inquiry on Shiradi Sai Baba cult which is popularizing worship tradition among people of India and Sri Lanka. The worship of Shiradi Sai Baba, which is emerging as a unique religious tradition in predominantly line with the Hindu religious tradition in Jaffna, creates a space for getting new religious experiences among the Hindu devotees. The objectives of this study is to analyse the unique features of the Shiradi Sai Baba cult and its socio-cultural importance in the Jaffna cultural domain and discuss the religious and social factors behind its dynamics. This study is based on the ethnographic method which is principal approach in the study of culture. The primary data for this study were collected through the fieldwork conducted in Shiradi Sai Baba shrines in Jaffna. Sai Mandri, one of the Shiradi Sai Baba worship center located at Navalar Road, Nallur has been selected as a sample study center for this study. A person born in an Islamic family of Shiradi village, Maharashtra State in India has been deified as a popular deity and worshiped in India and Sri Lanka. The devotees can directly involve in this worship practices by various manners, though it is associated with Hindu worship. This Shiradi Sai Baba worships lead to leave the traditional Hindu cultural manners specially the concepts of purity and impurity in ritual matters, and to a new state of worship patterns. Definitions related to the sanctity of religion in the Hindu cultural tradition have been followed very flexibly in the worship tradition of Sri Sai Baba. However, this study reveals that the worship of Shiradi Sai Baba, which is very much in tune with the Hindu cults, is making new changes in the religious beliefs and practices of the youth in Jaffna.
Keywords: Cult; Shirady Sai Baba; Syncretism